2021
DOI: 10.1080/07350015.2021.1927742
|View full text |Cite
|
Sign up to set email alerts
|

SVARs Identification Through Bounds on the Forecast Error Variance

Abstract: Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in der dort genannten Lizenz ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…However, as in the case where the normalising impulse response is directly bounded away from zero, the identified set obtained under some small lower bound on the FEVD will also be sensitive to the choice of this lower bound when the identified set is unbounded in the absence of this restriction (see Appendix A.5 for an analysis of this case in the context of the bivariate model). Volpicella (2022) proposes imposing bounds on the FEVD, where the bounds are elicited from a range of estimated DSGE models. However, if the assumptions underlying the DSGE models that are used to elicit these bounds lack credibility, the derived bounds on the FEVDs will also lack credibility.…”
Section: Bounds On the Forecast Error Variance Decompositionmentioning
confidence: 99%
“…However, as in the case where the normalising impulse response is directly bounded away from zero, the identified set obtained under some small lower bound on the FEVD will also be sensitive to the choice of this lower bound when the identified set is unbounded in the absence of this restriction (see Appendix A.5 for an analysis of this case in the context of the bivariate model). Volpicella (2022) proposes imposing bounds on the FEVD, where the bounds are elicited from a range of estimated DSGE models. However, if the assumptions underlying the DSGE models that are used to elicit these bounds lack credibility, the derived bounds on the FEVDs will also lack credibility.…”
Section: Bounds On the Forecast Error Variance Decompositionmentioning
confidence: 99%
“…We relate to Giacomini, Kitagawa, and Uhlig (2019) and Giacomini and Kitagawa (2021) in stressing the mapping from reduced form to structural parameters, but we concentrate on a single prior. Others have focused on how to shrink posterior bands associated with the NiWU prior; see, for instance, Antolín‐Díaz and Rubio‐Ramírez (2018), Amir‐Ahmadi and Drautzburg (2021), and Volpicella (2021).…”
Section: Introductionmentioning
confidence: 99%
“…Exploiting the insights of their global identification analysis, RWZ also develop efficient and practical algorithms to perform estimation and inference for structural parameters and impulse responses. Their analytical and computational innovations have been instrumental to recent developments in the literature, including set-identified SVARs (Arias et al (2018(Arias et al ( , 2021), Giacomini and Kitagawa (2020), Giacomini et al (2021b), Volpicella (2020), Amir-Ahmadi and Drautzburg ( 2021)), locally-identified SVARs (Bacchiocchi and Kitagawa (2020)), and SVARs with narrative restrictions (Antolín-Díaz and Rubio-Ramírez (2018), Giacomini et al (2021a)), to list a few. RWZ provide several different versions of the necessary and sufficient conditions for global identification.…”
Section: Introductionmentioning
confidence: 99%